Developing paraphalaenopsis labukensis (Shim, A. Lamb & C.L. Chan), an Orchid Endemic to Sabah, Borneo, asymbiotic seed germination and in vitro seedling development - Nurul Najwa Mohamad (Tanjung Malim, 2023)
Developing paraphalaenopsis labukensis (Shim, A. Lamb & C.L. Chan), an Orchid Endemic to Sabah, Borneo, asymbiotic seed germination and in vitro seedling development by Nurul Najwa Mohamad